Implementing Azure Active Directory Integration with an Existing Cloud Service - Vehniä, Ville Juhani (My University, 2020)
Training Simulator (TraSim) is an online, web-based platform for holding crisis management exercises. It simulates epidemics and other exceptional situations to test the functionality of an organization’s operating instructions in the hour of need. The main objective of this thesis is to further develop the service by delegating its existing authentication and user provisioning mechanisms to a centralized, cloud-based Identity and Access Management (IAM) service. Making use of a centralized access control service is widely known as a Single Sign-On (SSO) implementation which comes with multiple benefits such as increased security, reduced administrative overhead and improved user experience. The objective originates from a customer organization’s request to enable SSO for TraSim. The research mainly focuses on implementing SSO by integrating TraSim with Azure Active Directory (AD) from a wide range of IAM services since it is considered as an industry standard and already utilized by the customer. Anyhow, the complexity of the integration is kept as reduced as possible to retain compatibility with other services besides Azure AD. While the integration is a unique operation with an endless amount of software stacks that a service can build on and multiple IAM services to choose from, this thesis aims to provide a general guideline of how to approach a resembling assignment. Conducting the study required extensive search and evaluation of the available literature about terms such as IAM, client-server communication, SSO, cloud services and AD. The literature review is combined with an introduction to the basic technologies that TraSim is built with to justify the choice of OpenID Connect as the authentication protocol and why it was implemented using the mozilla-django-oidc library. The literature consists of multiple online articles, publications and the official documentation of the utilized technologies. The research uses a constructive approach as it focuses into developing and testing a new feature that is merged into the source code of an already existing piece of software.
Keywords: fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|